The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1989
DOI: 10.1101/gad.3.4.547
|View full text |Cite
|
Sign up to set email alerts
|

Structure, sequence, and position of the stem-loop in tar determine transcriptional elongation by tat through the HIV-1 long terminal repeat.

Abstract: The human immunodeficiency virus (HIV-1)-encoded trans-activator (tat) increases HIV gene expression and replication. Previously, we demonstrated that tat facilitates elongation of transcription through the HIV-1 long terminal repeat (LTR) and that short transcripts corresponding to prematurely terminated RNA are released and accumulate in the absence of tat. Here, using a transient expression assay, we tested clustered and compensatory mutations, as wall as 3' deletions, in the trans-acting responsive region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
350
2
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(374 citation statements)
references
References 64 publications
21
350
2
1
Order By: Relevance
“…In the absence of Tat, RNAPII transcribes up to 150 nucleotides past the transcriptional start site on the HIV LTR (50). Supporting this observation, recent genome-wide analyses revealed that pausing sites distribute over an extended distance after initiation (51).…”
Section: Discussionsupporting
confidence: 55%
“…In the absence of Tat, RNAPII transcribes up to 150 nucleotides past the transcriptional start site on the HIV LTR (50). Supporting this observation, recent genome-wide analyses revealed that pausing sites distribute over an extended distance after initiation (51).…”
Section: Discussionsupporting
confidence: 55%
“…Deletion of a 70 bp region containing this NRE increased promoter activity by 5-6-fold, and also suppressed the heterologous TK promoter in an orientation-independent but position-dependent manner. These observations led to the hypothesis that the silencer affects transcriptional elongation by premature termination [102], as has been identified in the c-myc [103], c-myb [104], HIV-1 and HIV-2 promoters [105] or by pausing RNA pol II as occurs in the Drosophila heat-shock protein 70 (HSP70) gene [106]. However, further evidence is required to substantiate this hypothesis.…”
Section: Position-dependent Silencers (Nres)mentioning
confidence: 98%
“…There are, however, clear differences between the TATand N-mediated antitermination processes. The X nut site will function as a discrete element when moved away from its cognate promoter, whereas TAT-mediated antitermination requires TAR to be located immediately adjacent to the HIV promoter (Selby et al, 1989), and it also remains unclear whether TAT acts to overcome specific termination signals in the HIV TAR region in a manner analogous to the antitermination of the prokaryotic terminators. Most of the recent evidence suggests that in the absence of TAT, LTR-initiated transcription terminates at many, possibly random, downstream sites (Lapsia et al, 1989;Marciniak and Sharp, 1991;Kessler and Mathew, 1992).…”
Section: Regulation Of Transcriptional Elongation In Hiv Expressionmentioning
confidence: 99%